A comparison between Japan and Norway regarding ILO Convention No. 169 - Uzawa, Kanako (Universitetet i Tromsø, 2007)
Who defines indigenous peoples, and in whose interests does the definition serve? If there is a definition that is regulated in relation to indigenous peoples, how much does it the protect rights of indigenous peoples? Considering these questions as my point of departure, I have chosen to do a comparative study on the Sami in Norway and the Ainu in Japan in the context of ILO Convention No. 169. There are great differences between the Sami and Ainu in terms of governmental policy, legal frameworks, institutional structures, levels of domestic and international movement, awareness of human rights, and social atmospheres, especially given the fact that Norway is the first country to ratify ILO Convention No. 169. A main focus of this thesis is to pursue understanding the causes of those differences as well as similarities focusing. Moreover, how ILO Convention No. 169 has or has not been implemented at the domestic and international level is another main focus in this thesis. The thesis relies on an interview method to clarify the facts, and draws upon different levels to illustrate the topic by using texts and by interviewing people who have various perspectives on the issue. For instance, I interviewed Sami representatives who have been involved with the process of ratification of the ILO Convention No. 169 at the international and domestic levels and the Ainu representatives who have dealt with the international and domestic issue. Also, the government officials and ILO representatives also provided a different perspective on this matter. Finally, the thesis concludes with description of the dilemma that has been created in the process of legal and political development of the Sami and Ainu, and it suggests possible solutions for these matters in the future. The thesis focuses mainly on the legal perspective; but also by using the author’s own subjective experience as a point of reference it brings into focus other dimensions of indigenous politics, knowledge, and reality.